1999
DOI: 10.1111/1467-9280.00103
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Competition as The Basis of Stroop Interference: Evidence From Color-Word Matching Tasks

Abstract: A color-word matching task was used to investigate the basis of Stroop interference. Subjects were shown a pair of stimuli: an ink color (e.g., a red bar) and a colored word (e.g., RED printed in red or blue) and decided whether the two items had the same meaning (meaning decisions) or whether they had the same surface color (visual decisions). In Experiment 1, the two stimuli were shown simultaneously, and conflicting visual information of the word (e.g., RED printed in blue, against a red bar) led to interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
5
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(125 citation statements)
references
References 23 publications
5
108
5
7
Order By: Relevance
“…Experiment 1A. In the meaning-comparison Stroop task, participants decided whether the color of a patch was the same as the meaning of a colored word while retaining in WM seven letters that were randomly renewed in each trial (5). That is, participants had to use verbal mechanisms to process the meaning of the target word in the Stroop task and to retain the letters in WM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiment 1A. In the meaning-comparison Stroop task, participants decided whether the color of a patch was the same as the meaning of a colored word while retaining in WM seven letters that were randomly renewed in each trial (5). That is, participants had to use verbal mechanisms to process the meaning of the target word in the Stroop task and to retain the letters in WM.…”
Section: Methodsmentioning
confidence: 99%
“…Stroop and other researchers (2)(3)(4) explained this interference with the automaticity hypothesis: Word reading is more automatic than color naming. According to this account, the more arduous, attentiondemanding process of color naming is hampered by the more automatic process of word reading (5). However, contrary to predictions from the word automaticity account, Stroop interference can be observed from color distractors in revised versions of the task (5,6).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Other investigators, however, have obtained data inconsistent with this hypothesis (e.g., Henik, Ro, Merrill, Rafal, & Safadi, 1999), and alternative explanations have been proposed such as attention modulation (e.g., Besner & Stolz, 1999;Walley, McLeod, & Khan, 1997), semantic interference effects (e.g., Luo, 1999), or a combination of several causes (Sharma & McKenna, 1998;O'Leary & Barber, 1993). However, most investigators appear to agree that the continuous flow of information between the stimulus evaluation and the response system, and the resulting response competition, plays at least a partial role in the RT delay associated with responding to incongruent stimuli (e.g., Kornblum, Stevens, Whipple, & Requin, 1999;Lu & Proctor, 1995;MacLeod, 1991;Cohen, Dunbar, & McClelland, 1990).…”
Section: The Spatial Stroop Taskmentioning
confidence: 98%
“…He concluded that interference was attributable to conflict occurring at the semantic-level representation. Importantly, the SOAs adopted by Luo (1999) were long, and thus he could not study the gradual implementation of controlled mechanisms necessary to execute the tasks.…”
Section: Introductionmentioning
confidence: 99%